An iTRAQ characterisation of the role of TolC during electron transfer from Shewanella oneidensis MR‐1. Issue 21 (18th October 2016) - Fowler, Gregory J. S.; Pereira‐Medrano, Ana G.; Jaffe, Stephen; Pasternak, Grzegorz; Pham, Trong Khoa; Ledezma, Pablo; Hall, Simon T. E.; Ieropoulos, Ioannis A.; Wright, Phillip C.
Abstract : Anodophilic bacteria have the ability to generate electricity in microbial fuel cells (MFCs) by extracellular electron transfer to the anode. We investigated the anode‐specific responses of Shewanella oneidensis MR‐1, an exoelectroactive Gammaproteobacterium, using for the first time iTRAQ and 2D‐LC MS/MS driven membrane proteomics to compare protein abundances in S. oneidensis when generating power in MFCs, and growing in a continuous culture. The regulated dataset produced was enriched in membrane proteins. Proteins shown to be more abundant in anaerobic electroactive anodic cells included efflux pump TolC and an uncharacterised tetratricopeptide repeat (TPR) protein, whilst the TonB2 system and associated uncharacterised proteins such as TtpC2 and DUF3450 were more abundant in microaerobic planktonic cells. In order to validate the iTRAQ data, the functional role for TolC was examined using a δTolC knockout mutant of S. oneidensis . Possible roles for the uncharacterised proteins were identified using comparative bioinformatics. We demonstrate that employing an insoluble extracellular electron acceptor requires multiple proteins involved in cell surface properties. All MS and processed data are available via ProteomeXchange with identifier PXD004090.